How does health consciousness influence attitudes of elderly people towards traceable agricultural products? Perspectives of the technology acceptance model. Issue 8 (21st August 2020) - Lin, Hung-Chou; Kuo, Su-Hui
Abstract: Recently, internet usage among elderly adults has been increasing and becoming more mainstream; with the ageing population in Taiwan, concerns over health are on the rise, and this is directly related to the products that people eat. The main objectives of this study were to develop an integrated extensibility model incorporating the technology acceptance model and to investigate the impact of health consciousness on elderly adults' acceptance of technology in relation to traceability information websites in Taiwan. This study used structural equation modelling to analyse the data. The results revealed that elderly people with high health consciousness and high perceived usefulness had more positive attitudes towards products than those with low health consciousness and low perceived usefulness, and those with high health consciousness and high perceived ease of use had more positive attitudes than those with low health consciousness and low perceived ease of use in relation to the agricultural product traceability system.